Multiple weak supramolecular interactions stabilize a surprisingly twisted As2L3 assembly - Pitt, Melanie A.; Zakharov, Lev N.; Vanka, Kumar; Thompson, Ward H.; Laird, Brian B.; Johnson, Darren W. (Chemical Communications, 2008)
A combined crystallographic, DFT and NMR spectroscopic study of a flexible As(2)(3) assembly reveals temperature dependent conformational behavior in solution and a highly asymmetric structure stabilized by As-pi and edge-to-face aromatic interactions.

Multipoint anchoring of the [2.2.2.2]metacyclophane motif to a gold surface via self-assembly: coordination chemistry of a cyclic tetraisocyanide revisited - Toriyama, Masaharu; Maher, Tiffany R.; Holovics, Thomas C.; Vanka, Kumar; Day, Victor W.; Berrie, Cindy L.; Thompson, Ward H.; Barybin, Mikhail V. (Inorganic Chemistry, 2008)
A one-pot transformation of bis(2-isocyano-3-methylphenyl)ethane affords gram quantities of 8,16,24,32-tetraisocyano[2.2.2.2]metacyclophane ( 3). The solid state structure of 3 is remarkably close to the lowest energy conformation found on the potential energy landscape for 3 by DFT. In solution, the structure of metacyclophane 3 is mobile but can be locked in a rectangular gauche- anti- gauche- anti conformation by coordination of the isocyanide substituents to the [W(CO) 5] units to give [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) ( 5). The tetranuclear [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) motif featured in crystallographically characterized 5 may be present in several insoluble complexes of 3 previously described as mononuclear eta (4) species. A self-assembled monolayer of metacyclophane 3 is formed upon exposing a solution of 3 to the gold(111) surface with no precautions to exclude air or light. The monolayer nature of the film was confirmed by optical ellipsometry. The isocyanide stretching band for 3 shifts from 2119 cm (-1) in solution to 2175 cm (-1) upon chemisorption to metallic gold. The FTIR spectrum of the film indicates interaction of 3 with the gold surface via all four of its isocyanide anchors. No gold-facilitated oxidation of the -NC junctions was detected under ambient conditions. The energy cost associated with accessing the conformations of 3 suitable for mu 4-eta (1):eta (1):eta (1):eta (1) interaction of the molecule with the Au(111) surface is under 8 kcal/mol, a value that can be easily offset by formation of a gold-isocyanide bond. Two different mu 4-eta (1):eta (1):eta (1):eta (1) coordination arrangements of 3 with respect to gold atoms on the (111) face of the fcc Au lattice are suggested.